(untitled) (Italian Journal of Public Health, 2010)
Objective: To examine reports of verbal and physical abuse from family caregivers of adults with severe physical, neurological and developmental disabilities, and examine possible associations of abuse with family caregiver adjustment. Design: Cross-sectional.Participants: 147 community-residing caregivers (129 women, 18 men) of adults with disabilities (66 men, 81 women). Measures: Caregiver burden, life satisfaction, depression, health complaints, supervision provided to a family member with a disability, and care-recipient agitation and functional impairment. A brief measure of verbal and physical abuse experienced over the previous year was administered to the caregiver. Results: 51% of the sample reported some form of abuse in the twelve months prior to assessment. Caregivers who reported some form of abuse reported significantly greater distress and burden than caregivers who did not report any abuse. Conclusions: Caregivers who experience verbal and physical abuse may be at risk for increased emotional difficulties and have a greater sense of caregiver burden than caregivers who do not experience abuse. These data indicate that clinicians should attend to incidents of verbal and physical abuse that may occur between caregiver - care-recipient dyads. Further research is required to determine the conditions under which such abuse is likely to occur.